The linkage between individual, group and organizational learning at a hospital - Galleli, Bárbara Dias; Fischer, André Luiz Luiz; Marques, Mario Ferreira; Melo, Milena; Pilli, Luis Eduardo (Revista de Administração da UFSM, 2019)
This article aims to analyze the relation between individual, collective and organizational levels of learning in a hospital. In order to meet this objective, according to previous studies, a quantitative survey was carried out, from the application of questionnaires, with the hospital nurses. The data were analyzed followed by the technic of structural equation modeling. The results demonstrate that learning in groups is related to the learning that occurs at the individual and organizational levels. However, individual learning was not significantly associated with organizational learning. Furthermore, it was found that the collective learning substantially influences the organizational learning, compared to individual learning. The results are consistent to those found in other similar studies.